Ultraselective and Highly Permeable Polyamide Nanofilms for Ionic and Molecular Nanofiltration. (7th October 2020) - Sarkar, Pulak; Modak, Solagna; Karan, Santanu
Abstract: Membranes with ultrahigh ion selectivity and high liquid permeance are needed to produce high‐quality product water with increased recovery and process efficiency in water desalination. The narrow pore size distribution and controlled surface charge in the separation layer of nanofiltration membranes significantly improve the ion selectivity through molecular sieving and Donnan exclusion of co‐ions. Here, the ultraselective and yet highly water permeable polyamide nanofilm composite nanofiltration membranes developed by precisely controlling the kinetics of the interfacial polymerization reaction by maintaining the stoichiometric equilibrium at the interface is reported. The kinetically favorable stoichiometric equilibrium condition prohibits the formation of aggregate pores in the nanofilm and leads to the formation of narrow network pores with a high surface negative charge. Nanofilms are designed with a controlled degree of crosslinking and made as thin as ≈7 nm to achieve increased water permeance. The ultraselective membranes exhibit up to 99.99% rejection of divalent salt (Na2 SO4 ) and demonstrate monovalent to divalent ion selectivity of >4000. The selectivity of these nanofilm composite membranes is beyond the permeance–selectivity upper‐bound line of the state‐of‐the‐art nanofiltration membranes and one to two orders of magnitude higher than the commercially available membranes with pure water permeances of up to 23 L m −2 h −1 bar −1 . The fabrication process is scalable for membrane manufacturing. Abstract : Ultraselective polyamide nanofilm composite membranes formed on the porous polymer support are highly selective towards divalent ions and small molecules. The membranes exhibit up to 99.99% rejection of divalent salt (Na2 SO4 ) and demonstrate monovalent to divalent ion selectivity of >4000. Nanofilms are prepared via surfactant‐assisted controlled interfacial polymerization by maintaining the stoichiometric equilibrium at the interface.